Implementasi manajemen strategi untuk meningkatkan efisiensi operasional pada bank syariah - Adzkiya, Hida Amalia (Maliki Interdisciplinary Journal, 2025)
This study aims to find out more about the Implementation of Strategic Management to Improve Operational Efficiency in Islamic Banks. Islamic banks face major challenges in increasingly tight competition and changing market dynamics. To maintain operational efficiency without ignoring sharia principles, the implementation of appropriate and targeted strategic management is very important. The implementation of this strategic management is not only aimed at increasing profitability, but also ensuring that every operational process is in line with sharia values. Operational efficiency can be improved through various steps such as the adoption of digital technology, optimization of human resources, and the implementation of risk management. Digital transformation, such as the use of cloud-based core banking and mobile banking, helps Islamic banks reduce operational costs and increase service speed. With proper strategic management, Islamic banks can maintain a balance between efficiency and sharia compliance, while increasing public trust. The method used in this study is a descriptive qualitative method. The data used is secondary data sourced from reading materials or quotes from books, articles, journals, or other relevant scientific works as references in this study, especially strategic management.